HIV infection is associated with an increased prevalence of coronary noncalcified plaque among participants with a coronary artery calcium score of zero: Multicenter AIDS Cohort Study (MACS). Issue 10 (13th May 2015) - Metkus, TS; Brown, T; Budoff, M; Kingsley, L; Palella, FJ; Witt, MD; Li, X; George, RT; Jacobson, LP; Post, WS
<x xml:space="preserve">Abstract</x> Objectives HIV‐infected individuals bear increased cardiovascular risk even in the absence of traditional cardiovascular risk factors. In the general population, coronary artery calcium (CAC) scanning is of value for cardiovascular risk stratification, but whether a CAC score of zero implies a low noncalcified coronary plaque burden in HIV‐infected persons is unknown. Methods We assessed the prevalence of noncalcified coronary plaque and compared noncalcified coronary plaque burden between HIV‐infected and HIV‐uninfected participants who had CAC scores of zero in the Multicenter AIDS Cohort Study (MACS) using coronary computed tomography (CT) angiography. Results HIV infection was associated with the presence of noncalcified coronary plaque among these men with CAC scores of zero. In a model adjusted only for age, race, centre, and pre‐ or post‐2001 cohort, the prevalence ratio for the presence of noncalcified plaque was 1.27 (95% confidence interval 1.04–1.56; P = 0.02). After additionally adjusting for cardiovascular risk factors, HIV infection remained associated with the presence of noncalcified coronary plaque (prevalence ratio 1.31; 95% confidence interval 1.07–1.6; P = 0.01). Conclusions Among men with CAC scores of zero, HIV infection is associated with an increased prevalence of noncalcified coronary plaque independent of traditional cardiovascular risk factors. This finding suggests that CAC scanning may underestimate plaque burden in HIV‐infected men.